Portuguese fertility transition and the multiple response system - Oliveira, I. T. (Journal of Family History, 2006)
This research analyzes the Portuguese fertility transition combining Davis’s multiphasic response perspective with Friedlander’s system of multiples responses. Interaction between fertility decline and traditional mechanisms of population growth control (the European marriage pattern and out-migration) is the main basis on which to explore Portuguese demography between 1920 and 1960. A geographical approach shows an association among high marital fertility, emigration, and low nuptiality; a chronological perspective reveals that migration has an increasing trend until fertility transition began and that female nuptiality remains low during this period and afterward. The multiple response perspective stresses path diversity during fertility transitions. Econometric models for regional diversity during fertility transition show migration and nuptiality importance in the Portuguese case. A comparative analysis confirms this idea for Spain, Italy, and Germany.